Ultrafiltration Failure Is a Reflection of Peritoneal Alterations in Patients Treated With Peritoneal Dialysis - Krediet, Raymond T. (Frontiers in Physiology, 2018)
Ultrafiltration failure is a common and important complication of peritoneal dialysis, especially in long-term patients without residual urine production, because it often causes overhydration, which is an important cause of death in this population. This review provides an overview of the pathways of peritoneal fluid transport, followed by the mechanisms and causes in ultrafiltration failure. The egression of fluid to the tissues and its re-uptake by the colloid osmotic pressure are markedly influenced by peritoneal dialysis, because the dialysis solutions contain glucose as an osmotic agent causing removal of fluid from the circulation by crystalloid osmosis. Pores involved in transcapillary ultrafiltration consist of inter-endothelial small pores and the intra-endothelial water channel aquaporin-1. The former allows transport of plasma fluid with dissolved low molecular weight solutes and accounts for 60% of the filtered volume, the latter transports 40% as pure water. This free water transport is driven by the crystalloid pressure gradient, while small pore fluid transport is also dependent on the hydrostatic pressure. The number of perfused peritoneal microvessels assessed by small solute transport parameters, is differently associated with ultrafiltration: a positive relationship is present with small pore fluid transport, but a negative one with free water transport, because the effect of more vessels is counteracted by a faster disappearance rate of glucose. Ultrafiltration failure can be present shortly after the start of peritoneal dialysis, sometimes due due to mesothelial-to-mesenchymal transition. Late ultrafiltration failure develops in 21% of long-term patients. Both transport modes can be affected. Patients with encapsulating peritoneal sclerosis have severely impaired free water transport, probably due to interference of interstitial collagen-1 with the crystalloid osmotic gradient. This may also apply to other patients with reduced free water transport. Those with impaired small pore fluid transport likely have a reduced hydrostatic filtration pressure due to vasculopathy. Deposition of advanced glycosylation end products is probably important in its development . Long-term ultrafiltration failure may affect both small pore fluid transport and free water transport. Vasculopathy is important in the former, interstitial fibrosis in the latter. Peritoneal transport measurements should include assessments of small pore-and free water transport.